Learning styles useful in improving students' learning / Mak Kem Seng - Mak, Kem Seng (Universiti Teknologi MARA Kedah, Sungai Petani, 2002)
This article provides an insight into learning styles, which could be useful for educators. It serves to present the theory and the operational aspects of learning styles identified among learners. Teaching and learning practices urgently need improvement. As such, learning styles is a concept that can be important and useful in enhancing our teaching practices. Successful learners employ different and more efficient learning styles during their learning process. Learners acquire expectations on their own efficacy of learning from their own individual learning styles. On the basis of this concept it is therefore pertinent that educators should learn to exploit the concept of learning styles and incorporate them into their lessons.